Inpatient hospital procedural volume and outcomes following catheter ablation of atrial fibrillation. (4th June 2020) - Cheung, Jim W.; Yeo, Ilhwan; Cheng, Edward P.; Ip, James E.; Thomas, George; Liu, Christopher F.; Markowitz, Steven M.; Kim, Luke K.; Lerman, Bruce B.
Abstract: Introduction: The real‐world distribution of hospital atrial fibrillation (AF) ablation volume and its impact on outcomes are not well‐established. We sought to examine patient characteristics, complications, and readmissions after AF ablation stratified by hospital procedural volume. Methods and Results: Using the nationally representative inpatient Nationwide Readmissions Database, we evaluated 54 597 admissions for AF ablation between 2010 and 2014. Hospitals were categorized according to tertiles of annual AF ablation volume. Index complications, 30‐day readmissions, and early mortality were examined. Multivariable logistic regression was performed to assess the predictors of adverse outcomes. Between 2010 and 2014, low volume tertile hospitals accounted for 79.3% of hospitals performing AF ablations. When stratified by first, second, and third volume tertiles, complication and early mortality rates were higher in low volume centers (8.9% and 0.67% vs 6.1% and 0.33%, vs 4.5% and 0.16%, respectively; P < .001). Patients undergoing AF ablation at low volume centers were older and had a higher prevalence of congestive heart failure, coronary artery disease, and other comorbidities. Low volume hospitals were associated with increased cardiac perforation (adjusted odds ratio [aOR], 4.79; P < .001), vascular complications (aOR 1.49; P < .001), and any complication (aOR 2.06; P < .001) during index admission as well as increased early mortality (aOR 2.43; P = .039). Conclusions: Among patients hospitalized for AF ablation, low inpatient AF ablation hospital volume was associated with worse outcomes following ablation, which was exacerbated by a greater comorbidity burden among patients at these centers.